ANALISIS PERUBAHAN IKLIM TERHADAP PRODUKSI PERKEBUNAN DI KOTA PEKANBARU - Afrizal Saputra (Pelantar Press, 2023)
Climate change is a matter of concern and a global issue that is being hotly discussed and must be done, the impact of climate change itself can affect various sectors, such as the economy, environment, and social climate. The city of Pekanbaru, which is located at the equator, is an area that is very influential on climatic conditions, one of which is rainfall. The Riau region in general has a large plantation area, in particular Pekanbaru has a plantation area of 28,434 hectares. Disturbance or climate change will affect rainfall conditions in the city of Pekanbaru, where the occurrence of this disturbance will have an impact on the results of plantations in the city of Pekanbaru, of course this will affect the economic conditions of the plantation owners, and of course it will also spread to environmental conditions where plantation land is opened. . It will be seen how much influence climate change has on plantation conditions in the city of Pekanbaru, through trend and correlation analysis it will be seen how the increase or decrease in plantationyields with rainfall.